An effector from the Huanglongbing-associated pathogen targets citrus proteases - Kelley Clark (Nature Portfolio, 2018)
Greening disease threatens the productivity of citrus crops worldwide yet the pathosystem is poorly understood. Here, Clark et al. show that an effector cloned from the associated bacteria can suppress host plant papain-like cysteine proteases' activity, suggesting its probable role in pathogenesis.